Effects of dacomitinib on the pharmacokinetics of poziotinib in vivo and in vitro - Weiping Ji; Jiquan Shen; Bo Wang; Feifei Chen; Deru Meng; Shuanghu Wang; Dapeng Dai; Yunfang Zhou; Changxiong Wang; Quan Zhou (Taylor & Francis Group, 2021)
Context Dacomitinib and poziotinib, irreversible ErbB family blockers, are often used for treatment of non-small cell lung cancer (NSCLC) in the clinic. Objective This study investigates the effect of dacomitinib on the pharmacokinetics of poziotinib in rats. Materials and methods Twelve Sprague-Dawley rats were randomly divided into two groups: the test group (20 mg/kg dacomitinib for 14 consecutive days) and the control group (equal amounts of vehicle). Each group was given an oral dose of 10 mg/kg poziotinib 30 min after administration of dacomitinib or vehicle at the end of the 14 day administration. The concentration of poziotinib in plasma was quantified by UPLC-MS/MS. Both in vitro effects of dacomitinib on poziotinib and the mechanism of the observed inhibition were studied in rat liver microsomes and human liver microsomes. Results When orally administered, dacomitinib increased the AUC, Tmax and decreased CL of poziotinib (p < 0.05). The IC50 values of M1 in RLM, HLM and CYP3A4 were 11.36, 30.49 and 19.57 µM, respectively. The IC50 values of M2 in RLM, HLM and CYP2D6 were 43.69, 0.34 and 0.11 µM, respectively, and dacomitinib inhibited poziotinib by a mixed way in CYP3A4 and CYP2D6. The results of the in vivo experiments were consistent with those of the in vitro experiments. Conclusions This research demonstrates that a drug-drug interaction between poziotinib and dacomitinib possibly exists when readministered with poziotinib; thus, clinicians should pay attention to the resulting changes in pharmacokinetic parameters and accordingly, adjust the dose of poziotinib in clinical settings.